Engineering geological and geotechnical investigations of dam of the Bunakha Hydroelectric Project (180 MW), Chukha Dzong, Bhutan Himalaya (Journal of Nepal Geological Society, 2014)
A 197 m high roller compacted concrete gravity dam is proposed across river Wang Chhu in Chukha Dzong of the Bhutan Himalaya. Bunakha Dam will be the third highest dam constructed by India after the Tehri Dam and Bhakra Dam. The Bunakha Dam site area is located in the Thimpu Formation of the Himalayan crystalline complex. This litho-units at site is characterized by heterogeneous lithology consisting of viz.  banded gneisses, foliated gneisses, with large boudins and bands of quartzite and calc-silicate gneisses with large porphyroblasts of garnet measuring up to 4 mm. These litho units form the foundation of proposed dam. In this paper attempt has been made to bring out the rock mass condition of the foundation of dam of the proposed scheme on the basis of detailed engineering geological mapping, geological logging of drill holes, rock mass permeability values, 3D mapping of exploratory drifts, geophysical profiling, in-situ andlaboratory test results. Rock mass classification using Rock Mass Rating (RMR) system and Q-system was done. The basic purpose of these investigations was to identify/map different rocks and structures like joints, shear zones, faults, fracture zones etc. and to determine engineering properties of rock and rock mass by laband in-situ testing and to provide basic data for economic and fail-safe design of the dam. On the basis of these investigations suitable recommendations have been made which will be helpful during the construction of the dam.